The Assessment of Website Design Quality in Thermal Tourism Industry: The Comparative Study for Turkish and German Thermal Hotels - Duygu Kocoglu; Suleyman Barutcu; Selcuk Burak Hasiloglu (European Scientific Journal, ESJ, 2017)
In the Internet Age, website design, content and efficiency are very important for customers and companies as well. Website design researches increasingly focused on design quality and contents in last years. In terms of the thermal hotel marketing perspectives, high website design quality and contents offer a number of advantages such as the opportunity to convince potential customers to select hotels and observe all thermal hotels services without staying there. However, thermal hotels are also work like health institutions. Their websites ought to allow their customers to access more health related information and serve as a platform for gaining access to healthcare information. Thus, they should be designed health oriented, instead of just marketing and public relations purposes. The main objectives of this study is to call website designers’ attention to thermal hotel website contents, and to compare the thermal hotels’ websites between Baden-Baden, Germany and Afyonkarahisar, Turkey destinations with Analytic Hierarchy Process (AHP) method. At the end of the study, the characteristics of the thermal hotels website design quality are discussed via AHP, and some recommendations are given to designers, hotel managers and public institutions responsible for health institutions related to thermal hotel website design requirements and standards.